Discovery of the male of the rare caligiform copepod Kabataia Kazachenko, Korotaeva & Kurochkin, 1972 (Copepoda: Siphonostomatoida), with a reconsideration of its phylogenetic affinities - Hutson, Kate S.; Boxshall, Geoffrey A. (Zootaxa, 2016)
We report the discovery of the male of the rare caligiform copepod Kabataia ostorhynchi Kazachenko, Korotaeva & Kurochkin, 1972 on the gills of the type-host Oplegnathus woodwardi (Waite, 1900) captured in the Southern Ocean, off Australia. Light and scanning electron microscopy confirmed the unusual body plan of Kabataia Kazachenko, Korotaeva & Kurochkin, 1972, where only the first pedigerous somite is incorporated into the cephalothorax and the second and third pedigerous somites are fused to form a double-somite, visible both dorsally and ventrally. The adult female carries paired dorsal plates originating from the second pedigerous somite within this double-somite. In the male the second and third pedigerous somites are free and paired dorsal plates are present on the former. Kabataia exhibits sexual dimorphism in an unusually wide range of limbs. Most remarkable is the tubular extension from the exit pore of the maxillary gland at the base of the maxilla which reaches beyond the anterior margin of the mouth tube; this is present in the male only. Kabataia exhibits a functional articulation between the first and second pedigerous somites and thus lacks the diagnostic apomorphy of the family Trebiidae (incorporation of both first and second pedigerous somites into the cephalothorax). We propose to transfer Kabataia to the Pandaridae, since it shares the key synapomorphies of this family. Furthermore, we propose to transfer Innaprokofevnas Kazachenko, 2001 to the Dissonidae, which leaves Trebius Krøyer, 1838 as the only genus within the Trebiidae. The correct spelling of Philorthragoriscus Horst, 1897 is noted.